2016
DOI: 10.1089/dia.2015.0180
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pumps in Type 1 Diabetes with Mental Disorders: Real-Life Clinical Data Indicate Discrepancies to Recommendations

Abstract: In routine diabetes care, CSII use and discontinuation vary widely among T1D patients with mental disorders and indicate clear differences from the latest recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 14 publications
1
33
1
Order By: Relevance
“…There was a high prevalence in social phobia, panic disorders or agoraphobia, psychological distress, OCD and GAD in type 1 patients with diabetes compared with type 2 [14][15][16]21,31,32]. Type 1 population with diabetes appears since childhood and it possible that increase in glucose and indicated as predictive of high anxiety [18,[23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There was a high prevalence in social phobia, panic disorders or agoraphobia, psychological distress, OCD and GAD in type 1 patients with diabetes compared with type 2 [14][15][16]21,31,32]. Type 1 population with diabetes appears since childhood and it possible that increase in glucose and indicated as predictive of high anxiety [18,[23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…As the results of this study showed, both types require a warning for the treatment of that emotional disturbance [14,15,26,32]. Worry about the future is common in patients with diabetes [14][15][16]21,31,32,33]. All of the time, they can get in troubles with effort, money, and stress have an emotional influence on individual stability and introduce psychiatry disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…fluoxetine and Prozac) as the use of antidepressant medication is strongly associated with depressed mood. This method has been applied successfully in previous studies on comorbid psychiatric disorders .…”
Section: Methodsmentioning
confidence: 99%